Developing a New Dimension for Fourier Domain Optical Coherence Tomography Images by Simultaneous Measurement of the Refractive Index and Thickness: True Physical Thickness Optical Coherence Tomography - Amjadi, Ahmad; Ghodsi , Hamed; Khandani , Salile; Khishkhah, Bahareh; Rajai, Payman; Razzaghi, Mohammadreza (Journal of Lasers in Medical Sciences, 2021)
Introduction: Fourier domain Optical coherence tomography (OCT) is a widely used highresolution optical imaging technique. It is useful for various applications in medical imaging, such as ophthalmology (e.g. retinal imaging for diagnosing complications like glaucoma or macular degeneration), dermatology, oncology, and cardiology. The ability to noninvasively measure both the refractive index and thickness of biological tissues could have various medical applications and enable earlier disease detection. For example, observing changes in the refractive index can help distinguish between tissues with normal or abnormal function. Methods: In this study, the theoretical framework for simultaneous measurement of the refractive index and physical thickness of multilayer systems is proposed and tested for two different samples, each having three layers, a glass/NaCl solution/glass sample and a glass/sugar solution/glass sample. The whole signal processing procedure and the experimental setup are described. Results: The refractive index and thickness of saltwater and sugar water samples in the Fourierdomain OCT (FD-OCT) system were obtained. The resulting data were compared with reference measurements and showed a deviation of about 1% for the samples. Conclusion: We tested the proposed framework for the simultaneous extraction of the refractive index and thickness of multilayer systems of salt water and sugar water from its FD-OCT data. We showed that the measured parameters were in agreement with reference amounts. DOI: 10.34172/jlms.2021.89